ANALISIS PERAN AKTOR IMPLEMENTASI DALAM KEBIJAKAN PENGELOLAAN SAMPAH DI KOTA SEMARANG - Reflay Ade Sagita; Ida Hayu Dwimawanti; Titik Djumiarti (Journal of Public Policy and Management Review, 2013)
Integrated waste management is necessary by an area to minimize the negative impacts from the poor waste management. There are some actors who contribute to achieve the objectives from the waste management in implementation of the waste management. Theroles between first actors with another actor are not the same, depending on their position in the public policy environment. There are 3 (three) main actors who play a role in implementation of waste management in Semarang, namely Government Bureaucracy, Community Groups and Private Parties.The purpose of research is to describe and analyze of actor role implementation in policy of waste management in Semarang. Find solution to the inhibiting factors on actorrole implementation implementing in policy of waste management in Semarang. The role of the actor can be seen 10 indicators according to the model Grindle.